Job burnout and employee commitment - Lukman, J.A.; Salman, A.; Olawale, Y.A. (Farabi Journal of Social Sciences, 2024)
Over the years, organizations have faced the challenge of employees’ lack of commitment due to job burnout, which can often be exacerbated by excessive workload. This study aims to investigate the effects of burnout and employee workload on employee commitment. Using a survey research design, the study focused on a population of 130 employees from the Coca-Cola Bottling Company in Ilorin. A simple random sampling technique was employed, allowing every member of the population an equal chance of being included in the study. The sample size of 120 was determined using the Taro Yamane sample size formula. Data were collected through a questionnaire, and the study utilized inferential statistics, such as regression analysis, to test the hypotheses. Descriptive statistics, including frequency tables, were used to analyze the demographic data of the respondents. The findings indicate that employee commitment is negatively affected by both job burnout and workload. Consequently, the study concludes that addressing burnout alone may not necessarily enhance employee commitment, underscoring the need for a more comprehensive approach to employee well-being and organizational culture. Keywords: employee commitment, employee well-being, employee workload, job burnout, and organizational culture.